2011
DOI: 10.3389/fmicb.2011.00124
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for Gonorrhea: Can We Rise to the Challenge?

Abstract: Immune responses to the gonococcus after natural infection ordinarily result in little immunity to reinfection, due to antigenic variation of the gonococcus, and redirection or suppression of immune responses. Brinton and colleagues demonstrated that parenteral immunization of male human volunteers with a purified pilus vaccine gave partial protection against infection by the homologous strain. However, the vaccine failed in a clinical trial. Recent vaccine development efforts have focused on the female mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
101
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 113 publications
(149 reference statements)
1
101
0
Order By: Relevance
“…Furthermore, natural gonococcal infection confers no protective immunity; as such, previously infected individuals remain susceptible to future infections (8). The ability of the gonococcus to phase and antigenically vary its surface structures is thought to contribute to its evasion of the host adaptive immune response (8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, natural gonococcal infection confers no protective immunity; as such, previously infected individuals remain susceptible to future infections (8). The ability of the gonococcus to phase and antigenically vary its surface structures is thought to contribute to its evasion of the host adaptive immune response (8,9).…”
mentioning
confidence: 99%
“…Furthermore, natural gonococcal infection confers no protective immunity; as such, previously infected individuals remain susceptible to future infections (8). The ability of the gonococcus to phase and antigenically vary its surface structures is thought to contribute to its evasion of the host adaptive immune response (8,9). Recent studies have also demonstrated that the gonococcus proactively skews the host response away from humoral immunity and toward innate immunity, which is to the pathogen's advantage (9).…”
mentioning
confidence: 99%
“…Treatment failures with the last viable class of antibiotics, third-generation cephalosporins, have been encountered in several countries (7,8). The development of a protective vaccine(s) is of paramount importance (9)(10)(11)(12)(13)). An exciting development in vaccine research has been the recent success of an experimental vaccine composed of membrane vesicles derived from N. gonorrhoeae FA1090 (14) coadministered with interleukin-12.…”
mentioning
confidence: 99%
“…Gonorrhea remains a major public health concern due to increasing Gc resistance to antibiotics, lack of protective immunity from prior infection, and no protective vaccine (2,3). The inflammatory response associated with gonorrhea leads to serious complications such as pelvic inflammatory disease and infertility (4).…”
mentioning
confidence: 99%